Advances in highly active one-carbon metabolism in cancer diagnosis, treatment and drug resistance: A systematic review - Liu, Shuang; Wang, Zheng-Miao; Lv, Dong-Mei; Zhao, Yi-Xuan (Frontiers in Oncology, 2022)
Study background objectives Cancer poses a significant health concern as it is incurable. Every year, research on how to treat and eradicate this chronic condition is done. This systematic review will unmask the recent developments concerning highly active 1C metabolism with regard to cancer diagnosis, treatment, and drug resistance. The significance of this study is rolling out evidence-based evidence on the importance of one-carbon metabolism in cancer diagnosis and treatment. Methods Eight randomized controlled trials (RCTs) were reviewed from five electronic databases – EMBASE, Scopus Review, Google Scholar, Web of Science, and PubMed. Outcomes from the eight studies were analyzed to paint a picture of the topic in question. While the Preferred Reporting Items for Systematic Reviews and Meta-Analysis’ (PRISMA) protocol guided the initial literature search, The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach informed quality assessments of the eligible studies. Conclusion Since its emergence in the 1980s, 1C metabolism has been investigated and broadened to capture essential aspects of cancer treatment, diagnosis, and drug resistance. The review found that metabolites like folic acid could be used to detect different types of cancer. The metabolic pathways could induce tumorigenesis and DNA methylation, hence drug resistance.